Recent advances in lanthanide spectroscopy in Brazil - Gonçalves e Silva, Fabiana R.; Capelo, Renato G.; Albuquerque, Rodrigo Q. (Journal of luminescence, 2016)
This review discusses recent advances in lanthanide spectroscopy involving luminescence applications carried out in Brazil. The revised topics include glasses, sol–gel, light-emitting diodes, nanoparticles, metal–organic frameworks, coordination polymers, thin films, energy transfer processes, upconversion and development of new theoretical tools. The important role played by Prof. Oscar L. Malta on this subject is evidenced by his many contributions to the broad range of investigations reported here and this review is dedicated to him, on the occasion of his 60th birthday. This review discusses recent advances in lanthanide spectroscopy.Revised topics include glasses, sol–gel, LEDs, energy transfer processes.This review is dedicated to Prof. Oscar Malta on the occasion of his 60th birthday.